Development of a PLC-Based Automated Bottling and Capping System for Enhanced Production Efficiency - Thongphanh, Phutsavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Within the beverage manufacturing sector, manual operations often slow down production and lead to inconsistent product quality. To mitigate these operational boundaries, this investigation focuses on the engineering, construction, and empirical assessment of an automated system designed specifically to control fluid dispensing and container sealing in a set sequence. The core control architecture utilizes an OMRON CP1L-EM Programmable Logic Controller (PLC) integrated with an OMRON NS5-SQ11-V2 Human-Machine Interface (HMI) to manage two main stations: a time-based liquid filling station and an automated capping station. Experimental results demonstrate significant performance enhancements across key metrics. In terms of volumetric dispensing precision, the centralized setup demonstrated substantial reproducibility, yielding a mean cycle duration of 5.003 s paired with a minimal temporal standard deviation of 0.018 s, thereby preserving a 100% operational accuracy metric. Regarding manufacturing capacity, the automated capping subsystem sustained an average throughput of 61.9 BPM, which nearly scales the baseline manual output (31.5 BPM) by a factor of two, while securing a 98% successful sealing rate. In conclusion, this study confirms that utilizing a unified PLC/HMI framework to integrate filling and capping stages significantly enhances both production speed and precision, providing a reliable and cost-effective automation solution for improving the operational efficiency of Small and Medium Enterprises in the beverage industry.